Role of SEC14-like phosphatidylinositol transfer proteins in membrane identity and dynamics - Montag, Karolin; Ivanov, Rumen; Bauer, Petra (Frontiers in Plant Science, 2023)
Membrane identity and dynamic processes, that act at membrane sites, provide important cues for regulating transport, signal transduction and communication across membranes. There are still numerous open questions as to how membrane identity changes and the dynamic processes acting at the surface of membranes are regulated in diverse eukaryotes in particular plants and which roles are being played by protein interaction complexes composed of peripheral and integral membrane proteins. One class of peripheral membrane proteins conserved across eukaryotes comprises the SEC14-like phosphatidylinositol transfer proteins (SEC14L-PITPs). These proteins share a SEC14 domain that contributes to membrane identity and fulfills regulatory functions in membrane trafficking by its ability to sense, bind, transport and exchange lipophilic substances between membranes, such as phosphoinositides and diverse other lipophilic substances. SEC14L-PITPs can occur as single-domain SEC14-only proteins in all investigated organisms or with a modular domain structure as multi-domain proteins in animals and streptophytes (comprising charales and land plants). Here, we present an overview on the functional roles of SEC14L-PITPs, with a special focus on the multi-domain SEC14L-PITPs of the SEC14-nodulin and SEC14-GOLD group (PATELLINs, PATLs in plants). This indicates that SEC14L-PITPs play diverse roles from membrane trafficking to organism fitness in plants. We concentrate on the structure of SEC14L-PITPs, their ability to not only bind phospholipids but also other lipophilic ligands, and their ability to regulate complex cellular responses through interacting with proteins at membrane sites.